The prevalence of psychological co-morbidity in people with vitiligo: a systematic review and meta-analysis - Osinubi, O.; Grainge, Matthew J.; Ahmed, A.; Batchelor, Jonathan M.; Grindlay, Douglas; Thompson, A.R.; Ratib, Sonia (Wiley, 2018)
Background: Vitiligo is a chronic disorder causing skin depigmentation with global prevalence varying from 0.2 to 1.8%. UK guidelines recommend assessment of psychological state during clinical evaluation of vitiligo. However, the prevalence of psychological co-morbidity in people with vitiligo has not been described. Objectives: We aimed to establish the prevalence of psychological symptoms or disorders in people with vitiligo and describe the outcome measures used. Methods: We performed a comprehensive search of MEDLINE, Embase, CINAHL and PsychInfo to identify observational studies assessing the prevalence of psychological symptoms or disorders (December 2016). DerSimonian and Lard random-effects models were utilized to estimate the overall pooled prevalence. Results: We identified 29 studies with 2530 people with vitiligo. Most studies included a measure of either depression (n=25) or anxiety (n=13).The commonest tools were the Hospital Anxiety and Depression Scale and the Centre for Epidemiology Studies Depression Scale. Ten studies provided information on thirteen other psychological outcomes. Pooled prevalence using depression-specific and anxiety-specific questionnaires was 0.29 (95%CI 0.21, 0.38) and 0.33 (95%CI 0.18, 0.49) respectively. Prevalence was lower for clinically diagnosed depression (0.21; 95%CI 0.15, 0.28) and anxiety (0.15; 95%CI 0.06, 0.24). When non-specific tools were used the prevalence remained similar for depression (0.27; 95%CI 0.08, 0.46) but increased for anxiety (0.46; 95% CI 0.39, 0.52). High heterogeneity was observed. Conclusions: A range of psychological outcomes are common in people with vitiligo. The prevalence of anxiety was influenced by type of screening tool, suggesting validation of psychological outcome screening tools in the field of dermatology.